Concessional financing windows or the need to reform the magic triangle - Benoît Chervalier (Fondation pour les études et recherches sur le développement international (FERDI), 2015)
This study is published in advance of the major negotiations which will take place during 2015 on reforming concessional financing, most notably the Third International Conference on Financing for Development in Addis Ababa, Ethiopia. While this conference aims to address the broader issues of financing, calculating concessionality and what should be considered official development assistance (ODA), by including within it the various financial instruments which boost development finance in a form other than grants or loans, the multilateral development banks (MDBs) have launched a review focusing more narrowly on the future of their concessional financing windows.The organisational framework for the concessional financing offered by MDBs is based on mobilizing donor contributions to generate resources which are allocated, in the form of grants or highly subsidized loans and based on performance, to recipient governments while meeting their debt sustainability level. This system was put in place around 15 years ago, and has since undergone a succession of only minor adjustments. Special waivers have also stacked up, producing an excessively complicated system. It is the structure of this system which now needs to be rethought. But reform must be comprehensive and based on the 'magic triangle' in which resource mobilization, allocation of resources and debt sustainability management are closely linked and achieve an overall balance.Resources from traditional donors appear to have reached a climax. After the significant increase in ODA during the 2000s, reaching US 135.2 billion in 2014, and a highly focused political agenda, political mobilisation became more diffuse and was made more difficult by the budgetary constraints experienced by the main donors. It can therefore be reasonably expected that the level of concessional financing will see weak growth during the next replenishment cycles, with the notable exception of multilateral organisations focusing on an issue which is an international political priority with leadership at the highest level. This was the case with the Green Climate Fund, which was able to get pledges up to US 10 billion in Lima in December 2014 for its first fundraising initiative, thanks in particular to decisive commitment from the G20 Heads of State and Government.In parallel, the allocation formula, the objective of which is to reward performingcountries, has become increasingly complicated. Reality (health and food crises, climate disruption, support for endemically fragile and vulnerable regions) has introduced, over the course of various replenishment cycles, a number of a posteriori adjustments – whether to allocate funding based on exceptional circumstances (the Crisis Response Window provided by the World Bank (WB) and the Asian Development Bank (AsDB) and the Fragile States Facility operated by the African Development Bank (AfDB)) or to target priorities such as the AfDB's regional integration projects. Since then, the stacking up of waivers and set asides has only made the allocation framework more cumbersome, rendering the whole system opaque and complex. There is a large volume of literature on this subject, demonstrating the need to take greater account of countries' structural vulnerability in a bid to make the system intrinsically fairer and more effective. The resources allocated through the current performance-based system represent slightly more than 50% of total resources.And more than half of recipient countries – whether International Development Association (IDA) or African Development Fund (ADF) – are fragile countries. This trend will grow over the next ten years.Debt sustainability remains a constant concern. Concessional loan maturities mean that it will be particularly from 2020–2025 that the significant rise in loans granted between 2005 and 2015, as a result of the increased resources made available to concessional financing windows, will have an impact on the public finances of borrowing countries. This situation may leave countries vulnerable to external shocks, all the more so in the case of those countries which also borrowed from capital markets but on much more expensive terms – these loans will mature at the same time.The acceleration of countries completing the debt cancellation processes (Heavily Indebted Poor Countries (HIPC) and Multilateral Debt Relief Initiative (MDRI)), combined with the acceleration of global economic changes, is generating a multitude of paradoxical situations where countries currently eligible for concessional financing windows can, at the same time, gain access to capital markets. The recent revision of credit policies allowing countries eligible for concessional financing to access non-concessional funds requires a comprehensive revision of classification and graduation procedures.While the arguments in favour of maintaining concessional financing are strong – according to WB estimates, extreme poverty will still affect 504 million people in 2025, 58 percent of whom will be in Sub-Saharan Africa (80.7 percent if India, the major source of poverty outside Africa, is excluded) – it is the way in which it is mobilized and allocated that needs to be fundamentally rethought.Concessional resources should not be only considered a liquidity tool but as well as an equity one. Four main avenues of reform could be explored (the detail of these proposals is given after the summary): (i) the mobilization of concessional financing should be based on high-level political consensus; (ii) the division of effort between development institutions should be rethought in order to identify obvious comparative advantages; (iii) the country classification needs to be improved and there should be an increased focus on financing sectorial priorities; (iv) the framework for allocation resources should be adjusted to take account of these changes.The proposed reforms of the magic triangle take account of the profound economic changes countries are experiencing, and the constraints faced by development institutions. But no reform is possible without the political will to lead it. It is therefore first and foremost for capitals and for shareholders to demonstrate the courage to lead an ambitious and strategic reform agenda for the next decade.
Keywords: 330